The effect of work satisfaction and organizational commitment on human resources performance at the provision and protocol section regional secretariat of Karo District - Novia Ruth Silaen (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2021)
This study with the title The Effect of Job Satisfaction and Organizational Commitment on Performance, which aims to determine the effect parsilally and simultaneously carried out by ttest and Ftest. From the research results determined that job satisfaction and organizational commitment have a positive influence on performance which is determined by tcount greater than ttable. Furthermore, by using the simultaneous test, the results show that Fcount is greater than the Ftable. For this reason, it is suggested to further improve job satisfaction and organizational because to achieve effective commitment on performance in providing services to the community there are still many other factors that can affect, for example, training, discipline and others.